Exploring Al-Azhar Interpretation: Buya Hamka's Intellectual Contribution to the Indonesian Interpretation Tradition - Nurur Rohmah Rasidi; Habibah Sufriani; Tasya Avanti Digdayani; Rezwandi, Rezwandi (Penerbit Hellow Pustaka, 2025)
This study aims to explore Buya Hamka's intellectual contribution through his famous tafsir work, Tafsir al-Azhar, in the Nusantara tafsir tradition. The research method used is a qualitative approach with library research. The results of the study show that Tafsir al-Azhar adopts the tahlili method with the tartib mushafi system, prioritising a contextual approach by integrating the characteristics of adab ijtima'i exegesis, which emphasises guidance on social life and religious morality. Buya Hamka's intellectual contribution in Tafsir al-Azhar gives a distinctive colour to the Nusantara tafsir tradition, namely with an approach that is both profound and practical, easy to understand and relevant to the people in a social and spiritual context. This enriches the Indonesian tafsir treasury and strengthens the intellectual identity of Islam in the Nusantara.